Political economy, public policy and monetary economics : Ludwig von Mises and the Austrian tradition - Ebeling, Richard M. (London ; New York : Routledge, 2010)
The book provides an analysis of the political economy, public policy conceptions and monetary economics of the Austrian School. The Austrian school originated in the late nineteenth century through the works of Carl Menger, Eugen von Bohm-Bawerk and Friederich von Wieser.
Includes bibliographical references and index.
lje 24/04/13
Loans
Keywords: Von Mises, Ludwig; Political planning; Monetary policy; Public policy; Austrian tradition; Austria